2021
DOI: 10.1177/11297298211022078
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ultrasonography for peripheral catheter insertion and catheter failure prevention in visible and palpable veins

Abstract: Background: The increase in the success rate of peripheral intravenous catheterization against a difficult intravenous access (DIVA) using ultrasonography is reported; however, reports related to the effectiveness of using ultrasonography in increasing the success rate for visible and palpable veins is limited. Furthermore, according to a previous study, first attempt success in catheterization contributes to low catheter failure incidence. Thus, we developed a catheterization method using ultrasonography for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Other definitions considered a history of DIVA (n = 1), the need for a rescue technique (n = 2), abandonment of the procedure (n = 1), no visible or palpable veins after placing a tourniquet (n = 1), procedure duration of more than 1 minute (n = 1), use of central venous access (n = 1), and failure after 2 or more (n = 1) or 3 or more (n = 2) insertion attempts (Table 1). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The literature review identified DIVA risk factors for a total of 15 628 patients, but the heterogeneity of collected risk factors was a constraint on the sample size available for each of the factors in the current analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other definitions considered a history of DIVA (n = 1), the need for a rescue technique (n = 2), abandonment of the procedure (n = 1), no visible or palpable veins after placing a tourniquet (n = 1), procedure duration of more than 1 minute (n = 1), use of central venous access (n = 1), and failure after 2 or more (n = 1) or 3 or more (n = 2) insertion attempts (Table 1). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The literature review identified DIVA risk factors for a total of 15 628 patients, but the heterogeneity of collected risk factors was a constraint on the sample size available for each of the factors in the current analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eight studies were conducted in the United States, [21][22][23][24][25][26][27][28] 3 studies in Japan, [29][30][31] 2 in Australia, 10,32 and 1 study each in the Czech Republic, 33 Denmark, 34 Italy, 35 and the Netherlands. 36 Study designs included 9 prospective observational cohort studies, 10,[24][25][26]28,29,31,32,36 2 randomized trials, 23,33 3 prospective pre-post studies, 27,30,34 and 3 retrospective chart audits. 21,22,35 Most were conducted in single inpatient facilities (82%); 1 was a multicenter study, 36 and 2 studies reported ultrasound outcomes in prehospital settings.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…21,22,35 Most were conducted in single inpatient facilities (82%); 1 was a multicenter study, 36 and 2 studies reported ultrasound outcomes in prehospital settings. 10,33 Settings included emergency department, [21][22][23][24][25]28,35 ward settings, [29][30][31] telemetry, 26 operating suite and radiology, 36 and mixed settings. 27,32,34 Adults were the focus patient population in 15 studies, with pediatrics included in 3 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations